Politeness and Genre in Tourism Emails: ESP Insights from Hospitality Communication - Ni Made Ayu Sulasmini; Naniana N. Benu (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
Email communication plays a central role in professional interaction within the tourism and hospitality industry, where transactional efficiency must be balanced with interpersonal rapport. This study examines the interaction between genre structures and politeness strategies in authentic tourism-related emails. Drawing on Swales’ (1990) Genre Analysis Framework and Brown and Levinson’s (1987) Politeness Theory, the study qualitatively analyzes eleven authentic emails exchanged between a Bali-based travel agency, hotel partners, and international clients. The analysis reveals a recurrent sequence of rhetorical moves, namely greeting, purpose statement, elaboration, request or confirmation, and closing, within which politeness strategies are systematically embedded. Positive politeness predominates through expressions of gratitude, inclusive pronouns, and affective tone, reflecting the service-oriented nature of hospitality communication. Negative politeness is employed to mitigate imposition in sensitive requests, while bald-on-record strategies occur in interactions characterized by established professional familiarity. These findings demonstrate that genre structures in tourism emails function not only as organizational frameworks but also as resources for relational work. The study contributes to English for Specific Purposes (ESP) by highlighting the pedagogical value of integrating genre-based instruction with pragmatic awareness to enhance learners’ intercultural and professional email communication competence in tourism and hospitality contexts.